UPAYA MENINGKATKAN DISPOSISI DENGAN PENDEKATAN OPEN ENDED PADA SISWA SMK KELAS X-RPL B - Nadilla Rustyani; Yani Komalasari; Martin Bernard; Padillah Akbar (Journal on Education, 2019)
This study aims to determine the increase in mathematical dispositions of students using the open ended approach. The method used in this study is a qualitative method and this type of research is classroom action research. The population of this study was all students of class X IT Development Vocational School while the sample was class X RPL B. Data were collected based on observations, notes in the field, instruments in the form of non-disposition mathematical questionnaire scale tests. Questionnaires given contain indicators of students' mathematical dispositions, namely (1) confidence (2) can express ideas (3) check back on work results (4) persistent and diligent when working on questions (5) enthusiasm and serious learning mathematics (6) expect metacognition. The results of this study indicate that the use of an open-ended approach in mathematics learning can improve the mathematical disposition of class X RPL B students without development.